Analysis Of Product Development Strategies: A Case Study On Manufacturing Industry In Cikarang - Dewi, Puput Saputri; Rohimah, Ai Ria; Jamaludin, Jamaludin; Wiyanto, Tri Ngudi (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to analyze the product development strategies employed by the manufacturing industry in Cikarang. Through a qualitative research approach, data were collected from several manufacturing companies in the area using in-depth interviews and observations. The findings highlight a variety of strategies being utilized, with a primary focus on meeting consumer needs. Specifically, there is a tendency to employ derivative product development strategies, supported by directives from top management. However, the greatest challenge in producing innovative products that differ radically lies in requiring significant investment in research and development, as well as creating a conducive organizational environment. This study provides valuable insights for the manufacturing industry in Cikarang and encourages further research to involve companies in a broader region as well as to deepen understanding of product development strategies in the service industry.